2017
DOI: 10.1021/jacs.6b13074
|View full text |Cite
|
Sign up to set email alerts
|

Mining 2:2 Complexes from 1:1 Stoichiometry: Formation of Cucurbit[8]uril–Diarylviologen Quaternary Complexes Favored by Electron-Donating Substituents

Abstract: A 1:1 binding stoichiometry of a host-guest complex need not consist of a single host and guest. Diarylviologens containing electron-donating substituents complexed with cucurbit[8]uril (CB[8]) in a 1:1 stoichiometry exhibit abnormally large binding enthalpies compared to typical enthalpy changes observed for 1:1 binary complexes. Here, several CB[8]-mediated host-guest complexes, which were previously reported as 1:1 binary complexes, are verified to be 2:2 quaternary complexes by a combination of isothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 43 publications
6
107
0
Order By: Relevance
“…In all cases we surveyed, charged substituents are distributed between both CB [8] rims as evenly as possible. While Scherman's guests 4a [24] and our Pt complexes 6a-6c and 7b form quaternary complexes with unevenc harged istributionsa tt he CB [8] rims, one can argue that stacked 2:2a ssemblies are typically more stable than unstacked ones (see Figure 10 a), as long as encapsulating the free moiety of one of the ditopic guests (labeled Gi nF igure 10 a) into the water-filled cavity of the binary complex (labeled H) is more favorable than switching from an even to an unevend istribution of charges. An interaction between ap ositive group and aC B[n]r im corresponds to an approximate 4kcal mol À1 gain in total free energy (at least in the case of CB [7]), [45,87] and the free binding energy of ag uest such as berberine( 1)i nto binary complex 1·CB [8]i sa pproximately 8-9kcal mol À1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all cases we surveyed, charged substituents are distributed between both CB [8] rims as evenly as possible. While Scherman's guests 4a [24] and our Pt complexes 6a-6c and 7b form quaternary complexes with unevenc harged istributionsa tt he CB [8] rims, one can argue that stacked 2:2a ssemblies are typically more stable than unstacked ones (see Figure 10 a), as long as encapsulating the free moiety of one of the ditopic guests (labeled Gi nF igure 10 a) into the water-filled cavity of the binary complex (labeled H) is more favorable than switching from an even to an unevend istribution of charges. An interaction between ap ositive group and aC B[n]r im corresponds to an approximate 4kcal mol À1 gain in total free energy (at least in the case of CB [7]), [45,87] and the free binding energy of ag uest such as berberine( 1)i nto binary complex 1·CB [8]i sa pproximately 8-9kcal mol À1 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that enhanced interactions between the U‐shaped guest and the inner wall of CB[8], as well as limited exposure of the alkyl chain to water, advantageously compensate conformational strain and Coulombic repulsion between the ammonium groups . Very recently, Scherman and co‐workers showed that electron‐rich diarylviologens 4 a (X=H, CH 3 , OCH 3 , SCH 3 , and N(CH 3 ) 2 , NHCOCH 3 ) form discrete 2:2 complexes with CB[8] instead of the expected dynamic oligomers (see Figure ) . The balance of positive charges between the carbonylated rims is again drastically uneven, with two pyridinium units interacting with one pair of portals, and none with the other pair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a hypsochromic shift of the (usually enhanced) emission is often found for 1 : 1 CBn-dye complexes, pointing towards polarity differences between bulk water and the CBn cavity. [128] Besides, chromophore deaggregation (preventing aggregation-caused quenching, ACQ) often leads to significant emission enhancement and absorbance spectra changes. [42,118,119,120,121,122,123,124,125,126,127] Pronounced colourswitching upon 2 : 2 complex formation with CB8 was found for aryl-viologen chromophores.…”
Section: Absorbance Fluorescence and Circular Dichroismmentioning
confidence: 99%
“…In this context, severale legant examples have been reported. [7][8][9] However,a ll complexes have been investigated only in solution,a nd X-ray crystal structures have never been available, although they are crucially important for providing direct evidencef or the binding stoichiometry and refined structuralp arameters in the solid state.…”
Section: Introductionmentioning
confidence: 99%